KERAGAMAN KERAPATAN KAYU BATANG DAN CABANG KOMUNITAS POHON DI HUTAN GUNUNG PAPANDAYAN, JAWA BARAT - Eka Fatmawati Tihurua; Endah Sulistyawati (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Wood density is the functional character which has important role in the function of ecosystem. Stem and branch wood density have different trait and effect on its ecosystem processes. The objectives of this research are to know the diversity of stem and branch wood density and to analyze whether branch wood density could be used to estimate stem wood density in the Mount Papandayan. Six plots of 0.1 ha at different sites (three plots each in interior and edge forest) were established. Branches were collected from trees with diameter at breast height larger than 10 cm, while stem wood density data were obtained from some wood density sources. Research results showed that stem wood density ranges were 0.35–0.82 g/cm3, while branch wood density ranges were 0.33–0.61 g/cm3. Average of branch wood density was lower (0.48 ± 0.09 g/cm3) than stem wood density (0.61 ± 0.1 g/cm3). Linear regression analysis indicated that branch wood density could be used to estimate stem wood density of trees in Mount Papandayan which is showed by R2 value and correlation coefficient of 0.28 and 0.55 (p value < 0.001) respectively.